A novel method for elimination of aflatoxin M1 in milk using Lactobacillus rhamnosus GG biofilm. (28th January 2019) - Assaf, Jean Claude; Khoury, André El; Chokr, Ali; Louka, Nicolas; Atoui, Ali
Abstract : This study aimed to develop a new method for detoxification of milk from aflatoxin M1 (AFM1) by using Lactobacillus rhamnosus GG biofilm. After inoculation of milk contaminated with AFM1 into L. rhamnosus GG biofilm, the unbound AFM1 was extracted and quantified by HPLC. The stability of the formed AFM1/biofilm complex using different AFM1 contamination levels of milk was also studied. We found that the percentages of bound AFM1 by L. rhamnosus GG biofilm reached up to 60.74%. While no significant difference in milk proteins content was observed after AFM1 binding, some changes in total dry matter and fat content were noticed.